(3fgGjI GdEMcGe aj eYQaI GdCMcGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3LYaQ Hf YHO GdMSjf GdWQjMjs)
(3ChdgG (B:s
(3cJGH GdRcGI, hajg ebGUO GdChd aj RcGI GdeGds
(3BNQgG (B:s
(3hGdHYV aj ZjQg HWd aj ZjQ GdLfS (B... (3gPG BNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B285s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis